Clinical Significance of HSCARG for Atherosclerotic Coronary Heart Disease and Reduced ROS-Oxidative Stress in in Vivo and in Vitro Models via p47phox by NF-κB Activity - Zhou,Xiaofang (2022)
ABSTRACT Introduction: Coronary heart disease (CHD) is a dynamic process in which there are interactions between endothelial dysfunction, oxidative stress, and inflammatory responses. The aim of the present study was to investigate the function and mechanism of HSCARG in the treatment of CHD. Methods: Male apolipoprotein E/low-density lipoprotein receptor-deficient mice were given a high-fat diet with 21% fat and 0.15% cholesterol for the in vivo model. Human umbilical vein endothelial cells were incubated with angiotensin II for the in vitro model. HSCARG expression was inhibited in patients or mice with CHD. Results: HSCARG reduced oxidative stress in mice with CHD. HSCARG also reduced reactive oxygen species (ROS)-oxidative stress in the in vitro model. HSCARG induced p47phox expression in the in vitro model by NF-κB activity. The regulation of nuclear factor kappa B (NF-κB) activity or p47phox expression participates in the effects of HSCARG in CHD. Conclusion: Altogether, our data indicate that HSCARG reduced ROS-oxidative stress in in vivo and in vitro models of CHD via p47phox by NF-κB activity and may be a clinical target for CHD.